Engineering Geological Investigation of Slow Moving Landslide in Jahiyang Village, Salawu, Tasikmalaya Regency - Dwi Sarah; M. R. Daryono (Indonesian Journal on Geoscience, 2012)
DOI: 10.17014/ijog.v7i1.133An understanding of landslide mechanism is imperative to determine the appropriate mitigation method. The slow moving landslide (creeping) which occurred in Kampung Salawangi, Jahiyang Village, Salawu Subregency, Tasikmalaya had caused economical and environmental losses due to the frequent active movement particularly following rainfall events. Engineering geological investigation and slope stability analysis were carried out in the studied area in order to elucidate the mechanism of the landslide. The engineering geological investigation consists of local topographical mapping, geotechnical drillings, hand borings, cone penetration, and laboratory tests. The slope stability assessment of the recent landslide was conducted by a finite element method. The results of engineering geological data analysis show that the studied area is composed of residual soils of soft to firm sandy silt and loose to compact silty sand and base rock of fresh to weathered volcanic breccias with groundwater level varying between 3 - 16 m. The engineering properties of the residual soils indicate that the sandy silt is of high plasticity and the shear strength properties of the sandy silt and silty sand show low value with effective cohesion of 6.0 - 21.74 kPa and effective friction angle of 12.00 - 25.980. The assessment of slope stability shows that the stability of the studied area is largely influenced by the rise of groundwater level marked by the decrease of safety factor and increase of slope displacement.